The Emerald guide to Zygmunt Bauman - Best, Shaun (Bingley, U.K. : Emerald Publishing Limited, 2020)
The influential sociologist and social theorist Zygmunt Bauman was a prolific commentator on contemporary social life. The extent and range of his published work is so vast that it is easy for the uninitiated reader to feel daunted by the sheer scale of works and where to begin. That is, until now. The Emerald Guide to Zygmunt Bauman is the first introductory guide to the work of Zygmunt Bauman, designed specifically for students and those new to his work. It provides a clear, comprehensive and authoritative overview of the emergence and development of key themes and arguments across the whole body of Bauman's work, from his early publications in Poland in relation to actually existing socialism, to his Marxist revisionism, his influential analysis of the Holocaust, and his contribution to ethics and critiques of modernity and liquid modern neoliberalism. Critically, the book also places Bauman's work in context by discussing the influence of his personal biography on his ideas. This book provides a firm foundation for the independent reading of Bauman himself and for exploring the many discussions and interpretations of his influential ideas. It is essential reading for readers in sociology, politics, history, law, religion and other areas of the social sciences to which Bauman made a contribution.
Chapter 1. Bauman in context -- Chapter 2. Bauman: life, career and politics -- Chapter 3. Arrival in Britain: the successful outsider? -- Chapter 4. Bauman as a critic of modernity -- Chapter 5. The postmodern turn -- Chapter 6. The liquid turn -- Chapter 7. Bauman on inclusion and exclusion -- Chapter 8. Care for the other -- Chapter 9. Bauman's legacy -- Appendix 1. Zygmunt Bauman -- Bibliography -- Appendix 2. Sources and further reading.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Bauman, Zygmunt, -- 1925-2017.; Biography & Autobiography, Social Scientists & Psychologists; Biography: science, technology & medicine